Attractiveness of various crude feed ingredients to juvenile olive flounder (Paralichthys olivaceus, Temminck & Schlegel) and its application to aquaculture. (2nd August 2020) - Jeong, Hae Seung; Choi, Dong Gyu; Lee, Ki Wook; Cho, Sung Hwoan; Lim, Sang Gu; Lee, Bong Joo; Hur, Sang Woo; Son, Maeng Hyun; Lee, Seung Hyung; Kim, Kang Woong
Abstract: The attractiveness of crude feed ingredients to olive flounder and effects of including feed ingredients showing strong feeding attractiveness in extruded pellet (EP) on performance of fish were determined. Four types of experimental EP were prepared to evaluate the effects of feed ingredient manipulation on performance of fish. Five per cent anchovy meal component of the control diet was substituted with an equal amount of jack mackerel meal, sardine meal and hydrolysed fish meal to create the JM, SM and HFM diets respectively. The diets were prepared in commercial form as EP. Jack mackerel meal produced the strongest feeding attractant responses of olive flounder, followed by sardine meal and hydrolysed fish meal. The greatest weight gain, feed consumption and condition factor (CF) were observed in fish fed the JM diet, followed by fish fed the SM, HFM and control diets, in that order in the 8‐week feeding trial. The dietary manipulation of feed ingredients performed in this study showed that the inclusion of ingredients with strong feeding attractiveness improved feed consumption and eventually accelerated the growth performance and CF of the fish.